2021
DOI: 10.1164/rccm.202008-3212oc
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Intensive Care for Patients with COVID-19 in England, Wales, and Northern Ireland

Abstract: Rationale: By describing trends in intensive care for patients with coronavirus disease (COVID-19) we aim to support clinical learning, service planning, and hypothesis generation. Objectives: To describe variation in ICU admission rates over time and by geography during the first wave of the epidemic in England, Wales, and Northern Ireland; to describe trends in patient characteristics on admission to ICU, first-24-hours physiology in ICU, processes of care in ICU and patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
108
1
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 125 publications
(117 citation statements)
references
References 17 publications
6
108
1
2
Order By: Relevance
“…This trend was mirrored in the frailty Data on length of stay over the study period are shown in the appendix (p 4). In those who died in hospital and those who survived to discharge, median length of stay increased steadily across the study period (March 1-14 to May 24-31), from 2 (IQR 0-5) to 10 (4-22) days in those who survived to discharge and from 4•5 (3-10) to 11 (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) days in those who died during their hospital stay. Across the whole study period, the median length of stay was 7 days (IQR 3-14).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This trend was mirrored in the frailty Data on length of stay over the study period are shown in the appendix (p 4). In those who died in hospital and those who survived to discharge, median length of stay increased steadily across the study period (March 1-14 to May 24-31), from 2 (IQR 0-5) to 10 (4-22) days in those who survived to discharge and from 4•5 (3-10) to 11 (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) days in those who died during their hospital stay. Across the whole study period, the median length of stay was 7 days (IQR 3-14).…”
Section: Resultsmentioning
confidence: 99%
“…However, the trend towards reduced morality rates over time has been shown in a cohort of patients with COVID-19 in critical care in England. 18 The Intensive Care National Audit and Research Centre (ICNARC) collects and analyses case-mix and outcome data for individual patients for all adult general intensive care units, as well as other critical care units, in England, Wales, and Northern Ireland. They found that, after adjusting for patient characteristics, 28-day COVID-19related mortality decreased from 43•5% in the pre-peak period (before March 29, 2020) to 34•3% in the postpeak period (April 16 to May 21, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Although the magnitude of this trend might seem difficult to explain, a study from the UK showed an 11•8% reduction in adjusted 28-day inpatient mortality over time for critically ill patients, with fewer intensive care unit admissions for those aged 75 years and older. 6 This raises the possibility that older adults might have remained in the community longer earlier in the pandemic, perhaps not reaching the hospital. For example, it appears that patients residing in care homes might have been less likely to be transported to a hospital setting, potentially accounting for a portion of the high mortality seen in care homes during the peak of the pandemic.…”
mentioning
confidence: 99%
“…I agree with Gattinoni that ventilator management is an important consideration in explaining the "dramatically different outcomes (20-80% mortality rates)" for patients with "an identical disease. " [5] Emerging data reveal a 41.9% decrease in the rate of endotracheal intubation between February-March and April-May, accompanied by a 20.9% decrease in 28-day mortality [6]. In science, arriving at answers is frequently less fructiferous than posing the right question.…”
mentioning
confidence: 99%